Productivity and learning effects of augmented reality head-mounted displays - Özgür Gürerk; Thomas Bohné; Guillermo Alvarez Alonso (Computers in Human Behavior Reports)
Augmented reality (AR) applications promise to substantially amplify human capabilities in a variety of industrial work contexts. However, there is a lack of repeated-measures studies on productivity effects of AR HMDs on humans doing real tasks in realistic industrial settings. Moreover, productivity is mostly measured as time to completion, but other important measures, such as quality and usability, are often not considered over time. To address this research gap, we carried out a repeated experiment with participants using AR HMDs for a real industrial repair task. We find that even though there are no immediate task efficiency gains, the use of AR HMDs results in significantly faster repairs over time. The use of AR HMDs also has an immediate and positive effect on work quality. However, this effect diminishes as participants gain more experience. Finally, we find that usability and comfort were no significant problems for the subjects in our experiment.